Production of solar abundances for nuclei beyond Sr: The s- and r-process perspectives - Busso, Maurizio M.; Kratz, Karl-Ludwig; Palmerini, Sara; Akram, Waheed; Antonuccio-Delogu, Vincenzo (Frontiers in Astronomy and Space Sciences, 2022)
We present the status of nucleosynthesis beyond Sr, using up-to-date nuclear inputs for both the slow (s-process) and rapid (r-process) scenarios of neutron captures. It is now widely accepted that at least a crucial part of the r-process distribution is linked to neutron-star merger (NSM) events. However, we have so far only a single direct observation of such a link, the Kilonova GW170817. Its fast evolution could not provide strict constraints on the nucleosynthesis details and in any case there remain uncertainties in the local r-process abundance patterns, which are independent of the specific astrophysical site, being rooted in nuclear physics. We therefore estimate the contributions from the r-process to the Solar System (S.S.) abundances, by the largely site-independent waiting-point concept, through a superposition of neutron- density components normalized to the r-abundance peaks. Nuclear-physics inputs for such calculations are understood only for the trans-Fe nuclei, hence we restrict our computations to the Sr-Pr region. We then estimate the s-process contributions to that atomic mass range from recent models of Asymptotic Giant Branch stars, for which uncertainties are known to be dominated by nuclear effects. The outcomes from the two independent approaches are then critically analyzed. Despite remaining problems from both sides, they reveal a surprisingly good agreement, with limited local discrepancies. These few cases are then discussed. New measurements in ionized plasmas are suggested as a source of improvement, with emphasis on β-decays from unstable Cs isotopes. For heavier nuclei difficulties grow as r-process progenitors lie far off experimental reach and poorly known branchings affect s-processing. This concerns primarily nuclei that are very long lived in the laboratory and have uncertain decay rates in stars, e.g. 176Lu and 187Re. New measurements are urgently needed for them, too.